Project-Based Scaffolding TPACK Model to Improve Learning Design Ability and TPACK of Pre-Service Science Teacher - Dewi, N. R.; Rusilowati, A.; Saptono, S.; Haryani, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Learning design abilities and TPACK are very much needed by prospective science teachers to prepare science learning in the 21st century. The specific objectives of this research were to analyze the improvement of the learning design ability and TPACK possessed by pre-service science teachers after taking lectures with the Project-Based Scaffolding TPACK (PBST) model and analyze the correlation between TPACK and learning design abilities. The research used was quantitative research with non-equivalent control group design. The samples selected were 4 classes of pre-service science teachers who were taking Science Learning Strategy and Design courses. The instrument used in this study consisted of a lesson plan assessment sheet and a TPACK evaluation test. Data analysis used was independent t test, N-Gain test, and bivariate correlation test using SPSS. The results showed that the experimental class obtained an increase in the high category on learning design ability and the medium category on TPACK. After being given PBST model treatment in the experimental class, there is a significant difference in the learning design ability and TPACK between the experimental and control classes. In addition, the results also show that there is a correlation between TPACK and learning design ability. The PBST model is expected to be a solution offer to prepare pre-service science teachers at higher education in line with the demands of 21st century learning based on technology integration.